2013
DOI: 10.1002/cbic.201300029
|View full text |Cite
|
Sign up to set email alerts
|

A TR‐FRET‐Based Functional Assay for Screening Activators of CARM1

Abstract: Epigenome is an emerging field that demands selective cell-permeable chemical probes to perturb, especially in vivo, the activity of specific enzymes involved in modulating the epigenetic codes. Coactivator Associated Arginine (R) Methyltransferase 1 (CARM1) is a coactivator of estrogen receptor α (ERα), the main target in human breast cancer. We previously showed that overexpression of CARM1 by two-fold in MCF7 breast cancer cells increased the expression of ERα-target genes involved in differentiation and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…For instance, normal developmental functions were maintained in genetically engineered CARM1 hypomorphic mice with only 25% of the wild-type (WT) CARM1 level (Kim et al, 2010). We recently showed that knocking down 90% of endogenous CARM1 in MCF7 cells only slightly reduces methylation of PABP1 (Zeng et al, 2013). These results imply that even greatly depleted CARM1 catalytic activity and substrate methylation are sufficient to maintain major biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, normal developmental functions were maintained in genetically engineered CARM1 hypomorphic mice with only 25% of the wild-type (WT) CARM1 level (Kim et al, 2010). We recently showed that knocking down 90% of endogenous CARM1 in MCF7 cells only slightly reduces methylation of PABP1 (Zeng et al, 2013). These results imply that even greatly depleted CARM1 catalytic activity and substrate methylation are sufficient to maintain major biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…For more potent CARM1 substrates, such as histone H3 and PABP1, the C-terminus of CARM1 may be dispensable for their methylation. For example, we have shown that even when CARM1 was reduced to 10 % of endogenous level in MCF7 cells, CARM1-mediated methylation of PABP1 was not strikingly affected [61]. Co-crystal structures of full-length CARM1 with some substrates will help to elucidate whether the role of the C-terminus in regulating CARM1 substrate binding is substrate specific.…”
Section: O-glcnacylation Fine-tunes Carm1 Function By Regulating Subsmentioning
confidence: 99%
“…Advantages of collecting binding data include the ability to use cells during the growth phase, enabling for faster experiments and larger volumes, and flexibility in culture equipment. High-throughput screening methods have been extensively used for receptor-ligand binding data[5759], and would ideally be used to screen for more advantageous ligand/cell pairings. Transport studies, despite being limited to specialized Transwell® trays and requiring longer culture periods, provide more direct data for drug-delivery studies, and can be tested alongside passive transport for comparison.…”
Section: Discussionmentioning
confidence: 99%